Publisher Correction: Enabling “lithium-free” manufacturing of pure lithium metal solid-state batteries through in situ plating - Michael J. Wang (Nature Portfolio, 2020)
A Correction to this paper has been published: https://doi.org/10.1038/s41467-020-20374-y